Advances in CO2 gasification reactivity of biomass char through utilization of radio frequency irradiation. (15th December 2015) - Lahijani, Pooya; Mohammadi, Maedeh; Zainal, Zainal Alimuddin; Mohamed, Abdul Rahman
Abstract: A straightforward and well-known reaction for CO2 activation is the "Boudouard reaction", wherein, CO2 is reacted with carbon (char) to produce CO. In this study, a RF (radio frequency) heating system was developed to perform the Boudouard reaction by passing CO2 through a packed bed of PNS (pistachio nut shell) char. High CO2 conversion of 84% was achieved at 850 °C. When similar experiments were performed in thermal electric furnace, the conversion was only 38%. For further expanding the knowledge on RF-induced gasification, sodium (Na) was incorporated into char skeleton and gasified with CO2 under RF irradiation. RF gasification of Na-catalyzed char pronouncedly improved in the reaction, where sustainable CO2 conversion of 99% was attained at 850 °C. The predominance of RF over thermal heating was highly reflected in kinetic studies, where the activation energies of 26.7, 46.9 and 183.9 kJ/mol were obtained for catalytic and non-catalytic RF and thermal gasification, respectively. In RF gasification studies, it was attempted to improve the quality of mix gases, simulating air and steam gasification gas compositions, through the Boudouard reaction. The heating value of the gases simulating air and steam gasification improved from 6.4 to 8.0 MJ/m 3 and 7.6–10.4 MJ/m 3, respectively. Highlights: We study radio frequency-induced CO2 gasification of pistachio nut shell char. We achieve very high CO2 conversion of 99% in RF gasification of Na-catalyzed char. E a of 47 and 184 kJ/mol obtained for RF-assisted and conventional CO2 gasification. Heating value of synthesis gas improved via RF-induced char-CO2 gasification.